(untitled) (World Bulletin of Management and Law, 2024)
Through this article, some opinions were expressed on the structural and organizational aspects of non-governmental non-profit organizations, the foundations of the organization of non-governmental non-profit organizations, as well as how they are legally regulated in other countries.